Paleopathological evidence of Legg-Calve’-Perthes from the medieval cemetery of St. Agostino in Caravate, Northwestern Italy - Fusco, Roberta; Tesi, Chiara; Omar, Larentis (Medicina Historica, 2022)
Legg-Calvé-Perthes (LCPD) is a rare childhood disorder that induces the osteochondrosis of the femoral head. Almost all authors agree that the condition involves the obstruction to the bloody supply of the growing femoral head. The etiology is debated, as some authors claim that the triggering process of LCPD is unknown. Others argue that the onset of this affection can be prompted by several factors such as exogenous causes, trauma, metabolic issues, hematological disease, infections. LCPD has been recognized in archaeological material for nearly a century. The signs of the pathology are well described in the literature, but few paleopathological cases have been described. Here we report morphologic analyses of a skeleton retrieved during the archaeological investigations of the medieval cemetery of the church of St. Agostino in Caravate (Varese, Italy, 12th and 13th centuries). After an accurate differential diagnosis, the observed features suggest a conclusion of avascular necrosis of the right femoral head and unilateral evidence of LCPD.